Physical Activity as Prevention to Weight Gain: Awareness Among Selected Middle-Aged Faculty of the West Visayas State University (American Journal of Physical Education and Health Science, 2023)
This study sought to determine respondents’ level of awareness of physical activity as a prevention to weight gain among selected middle-aged faculty of the West Visayas State University, the academic year 2009-2010. The descriptive method of research was used in this investigation. The 60 selected middle-aged faculty of the West Visayas State University were the study’s respondents. They were taken as an entire group and classified as to age and gender. The standard deviation, mean and t-test set at .05 level of significance, were the statistical tools utilized to interpret the data. The findings revealed that when taken as an entire group and classified as to age and gender, both male and female respondents had a “highly aware” level of awareness. No significant differences were found on the level of awareness as the prevention to weight gain when respondents were classified as to age and gender.